Simulation for heating system indirectly connected to the secondary heating system - Wang, H.; Liu, Z.; Hao, Hong (Editorial Department of Journal of Shenyang Jianzhu University, 2015)
The aim of this paper is to study the large thermal hysteresis of district heating systems, so as to provide some theoretical supports for demand heating. Taking a residential district in Shenyang as the research object, based on the principle of heat transferring and the law of conservation of mass and energy, a mathematical model for the secondary network of indirectly connected district heating system was built and temperature responses were simulated and dynamical characters were also observed using MATLAB/Simulink. It is found that at the time of 15 h, the outdoor temperature rapidly increases form -16.8? to -5?. The indoor temperature reaches stability about in 4 hours. The return water temperature of the heat exchanger is in stability about in 5.5 hours and the supply water temperature reaches stability about in 6.5 h. The supplying heat exceeds 500 kW. Conclusion is that the district heating system has a large thermal hysteresis. It cannot adjust heating load according to the outdoor temperature. In order to achieve heat requirements of users, it requires timely and accurately forecast load for heating system to guide adjustment of heating system, so as to realize demand heating.